Hide Secret Messages in Raster Images for Transmission to Satellites using a 2-D Wavelet Packet - Khodher, Maisa’a Abid Ali (Iraqi Journal of Science, 2018)
The hiding of information has become of great importance in recent times. With dissemination through the internet, and communication through satellites, information needs to be secure. Therefore, a new algorithm is proposed that enables secret messages to be embedded inside satellite images, wherein images of any size or format can be hidden, using a system’s image compression techniques. This operation is executed in three main steps: first phase – the original image is converted into a raster image; second phase– steganography, in which a binary secret message is hidden inside a raster image, using a 4×4 array as the secret key; and third phase– compression of the stego-image raster in L2 and L3 using a 2-D wavelet packet. The outcome is a highly efficient algorithm, which can rapidly conceal information inside transmitted satellite images, thus guarding against revealing information to potential cyber-attackers.